2010
DOI: 10.1097/moo.0b013e3283405e48
|View full text |Cite
|
Sign up to set email alerts
|

Laryngomalacia: factors that influence disease severity and outcomes of management

Abstract: Most with laryngomalacia will have mild to moderate symptoms and not require surgical intervention. Those with GERD/LPR have symptoms improvement from acid suppression therapy. Those with severe enough disease to require supraglottoplasty will have minimal complications and good outcomes if multiple medical co-morbidities are not present. Those with multiple medical co-morbidities could be offered supraglottoplasty as the first intervention but counseled that tracheostomy may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
134
6
14

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(158 citation statements)
references
References 41 publications
4
134
6
14
Order By: Relevance
“…In our series, the patient with Smith-Magenis syndrome (patient 1) presented with a massively overhanging epiglottis. According to Landry et al [16], this type of laryngomalacia is more often observed in infants with severe forms and this condition seems challenging to treat, epiglottopexy being of limited success [26].…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the patient with Smith-Magenis syndrome (patient 1) presented with a massively overhanging epiglottis. According to Landry et al [16], this type of laryngomalacia is more often observed in infants with severe forms and this condition seems challenging to treat, epiglottopexy being of limited success [26].…”
Section: Discussionmentioning
confidence: 99%
“…Thompson (21) stated that severe laryngomalacia could be mentioned in the presence of inspiratory stridor accompanied with cyanosis and apnea, oxygen saturation level of 86% and lower at rest, recurrent aspirations, and growth-developmental retardation. Furthermore, they emphasized that these patients were candidates for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1, Video 1). Abnormal neuromuscular tone of the supraglottic larynx is the prevailing theory for the etiology of LM [8]. Infants with LM usually present at the age of 1-6 months with inspiratory stridor since birth or shortly thereafter that worsens with feeding, agitation, or supine positioning.…”
Section: Treatment Congenital Laryngomalaciamentioning
confidence: 99%
“…Ten to 20 % of children presenting with LM will require surgical intervention for severe airway obstruction resulting in apneas, blue spells, feeding difficulties, and failure to thrive, while others may be treated conservatively with medical management of reflux and close observation [8,10]. These patients undergo intraoperative microlaryngoscopy with bronchoscopy and demonstrate evidence of supralaryngeal prolapse upon inspiration (Video 2).…”
Section: Treatment Congenital Laryngomalaciamentioning
confidence: 99%
See 1 more Smart Citation